Preparation of Magnetic CuFe2O4@Ag@ZIF-8 Nanocomposites with Highly Catalytic Activity Based on Cellulose Nanocrystals - Sufeng Zhang; Yongshe Xu; Dongyan Zhao; Wenqiang Chen; Hao Li; Chen Hou (Molecules, 2019)
A facile approach was successfully developed for synthesis of cellulose nanocrystals (CNC)-supported magnetic CuFe2O4@Ag@ZIF-8 nanospheres which consist of a paramagnetic CuFe2O4@Ag core and porous ZIF-8 shell. The CuFe2O4 nanoparticles (NPs) were first prepared in the presence of CNC and dispersant. Ag NPs were then deposited on the CuFe2O4/CNC composites via an in situ reduction directed by dopamine polymerization (PDA). The CuFe2O4/CNC@Ag@ZIF-8 nanocomposite was characterized by TEM, FTIR, XRD, N2 adsorption-desorption isotherms, VSM, and XPS. Catalytic studies showed that the CuFe2O4/CNC@Ag@ZIF-8 catalyst had much higher catalytic activity than CuFe2O4@Ag catalyst with the rate constant of 0.64 min−1. Because of the integration of ZIF-8 with CuFe2O4/CNC@Ag that combines the advantaged of each component, the nanocomposites were demonstrated to have an enhanced catalytic activity in heterogeneous catalysis. Therefore, these results demonstrate a new method for the fabrication of CNC-supported magnetic core-shell catalysts, which display great potential for application in biocatalysis and environmental chemistry.